Jarmark św. Dominika '98 - Bogusławski, Tomasz (1958- ).; Treppa, Zbigniew (1960- ). ([S.l. : s.n.], 1998)
Plakat Jarmarku. W lewym dolnym nazwiska autorów.
Keywords: Jarmarki -- Polska -- Gdańsk -- 1945-1990.